Empowering Patient Self-Management: A Community Paramedicine Model of Care in Ontario - Sarah Turner (McMaster University Library Press, 2022)
Community Paramedicine Remote Patient Monitoring (CPRPM) was launched in Ontario in April 2015 to address high health system usage in vulnerable patients living with chronic disease.  CPRPM expands on the home visit model of community paramedicine (CP) to bridge gaps in patient care and address inefficiencies in resource utilization.  At patient and systems levels, CPRPM aims to promote patient self-management of chronic diseases. Several reports driving the development of the Ontario Seniors Strategy, which include key recommendations for expanding CP programs, provided the impetus for government to deliver on their electoral platform promise to increase health care spending. The Local Health System Integration Act, 2006 gave Local Health Integration Networks the authority to make home and community care services accessible to Ontario residents, including the supplies and equipment required by patients and their caregivers to support their care at home.  Outcome measures of CPRPM point to positive benefits for encouraging patient self-management of chronic diseases and reducing health system strain, with a return on investment of 542%.  The variety of options for patient interaction and ability to lessen health system burden makes CPRPM a desirable model of care.